The Effects of Gender, and Functional and Cognitive Training on Postural Control in Middle-Aged People - Mandana Sangari; Seyed Mohammadkazem Vaez-Mousavi; Mahdi Namazizadeh (Vesnu Publications, 2018)
Introduction: Postural control changes with ageing, and it is essential to study aging-related mechanisms. The aim of this research was to investigate the effects of gender, and functional and cognitive training on balance control in middle-aged people. Materials and Methods: This was a practical study with subimpirical method. The participants were 80 middle-aged people (40 men and 40 women), who were selected according to inclusion criteria, and randomly assigned to eight groups of internal and external focus guidelines in cognitive and functional supra-postural tasks. The postural status was evaluated by measuring the alignment of centre of gravity (COG) through a master balancing system using modified clinical test of sensory interaction and balance (mCTSIB). Results: Based on one-way analysis of variance, men and women who took the focal point of external attention in both functional and cognitive tasks had better postural control (P = 0.002). Men with external focus in functional task had better postural control than the other groups, and Women with internal focus in cognitive tasks had the weakest postural control function. Totally, men in functional and cognitive tasks had a better postural control function than women (P = 0.002). Conclusion: Adopting functional supra-postural strategy is better than cognitive supra-postural strategy in both middle-aged men and women in order to maintain balance. Regarding the fact that women with cognitive tasks with internal focus showed a significant difference in postural control than other groups, it is advisable to focus on stress management methods under stressful conditions for instructors. It seems that these findings are useful for mentors and therapists to design equilibrium exercises by considering age, gender, and type of attention instruction to avoid falling and performing dual tasks.